Field estimation of induction motor performance using dynamometer method and equivalent circuit method - Mohd Ariff, Mohd Hisyam (2008)
Three phase AC induction motors are ideal for most industrial and agricultural applications because of their simple construction, low maintenance and robustness in field conditions. With varying load requirements, the performance of the motor also varies in terms of torque, efficiency and power factor. The induction motor's performance characteristics provide important information to the motor designer and also to the actual users for evaluating operating costs and monitoring motor performance under actual load conditions. Realizing the importance of motor performance information in practice, this project aimed to investigate and improve the standard motor tests that predict motor performance so that it can be done quickly, easily and accurately. The first method is based on the dynamometer approach and the second is concerned with obtaining the motor's equivalent circuit parameters from basic tests. The performance of the motor in terms of torque, efficiency and power factor is then calculated from the equivalent circuit. The validity of the test methodology was verified by comparing the results of analysis with data of a motor from a catalogue with the results of dynamometer instrument in the laboratory. Also carried out in this project was motor performance analysis using GUI performance calculator which was developed using Matlab software. The results from the methods used were then compared in term of ease of implementation and accuracy achieved.